2006
DOI: 10.1093/eurheartj/ehl135
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized study comparing amiodarone vs. amiodarone plus losartan vs. amiodarone plus perindopril for the prevention of atrial fibrillation recurrence in patients with lone paroxysmal atrial fibrillation

Abstract: The results of this study suggest that the combination of perindopril or losartan with low-dose amiodarone is more effective than low-dose amiodarone alone for the prevention of AF recurrence in patients with lone paroxysmal AF. Adding losartan or perindopril to amiodarone can inhibit left atrial enlargement in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
1
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 25 publications
1
81
1
6
Order By: Relevance
“…(Table 2). In another study, 59 the beneficial effects of RAAS blockade with valsartan or ramipril over amlodipine in hypertensive patients with paroxysmal AF persisted even in the absence of concurrent antiarrhythmic drug. In these studies, there were no significant differences in the BP control between patients assigned to ACEIsor ARBs-based therapy as compared with other antihypertensive agents, mainly calcium channel blockers, suggesting the beneficial effects of ACEIs and ARBs on AF prevention were beyond their BP lowering effect.…”
Section: Raas Activationmentioning
confidence: 97%
“…(Table 2). In another study, 59 the beneficial effects of RAAS blockade with valsartan or ramipril over amlodipine in hypertensive patients with paroxysmal AF persisted even in the absence of concurrent antiarrhythmic drug. In these studies, there were no significant differences in the BP control between patients assigned to ACEIsor ARBs-based therapy as compared with other antihypertensive agents, mainly calcium channel blockers, suggesting the beneficial effects of ACEIs and ARBs on AF prevention were beyond their BP lowering effect.…”
Section: Raas Activationmentioning
confidence: 97%
“…7 Previous meta-analyses based on several post hoc analyses of randomized controlled trials have shown that RAS blockers significantly reduced the risk of new-onset AF ranging from 28% to 49%, but this benefit was limited to patients with systolic left ventricular dysfunction or hypertension with LVH. 10,11 For secondary prevention of AF, several relatively small prospective randomized studies [12][13][14] have demonstrated that therapies with ACEI/ARBs conferred an additional benefit on risk of recurrent AF in these patients when coadministered with antiarrhythmic drug therapy, usually amiodarone, compared with antiarrhythmic drug alone. Whether RAS blockade could prevent recurrent AF in paroxysmal AF patients with minor underlying cardiac pathology, who are not undergoing cardioversion and do not receive antiarrhythmic drugs therapy or ACEIs, remains controversial.…”
Section: Main Findingsmentioning
confidence: 99%
“…The group on enalapril showed a higher probability of remaining in sinus rhythm at four weeks (84.3% vs 61.3%, P = 0.002) and at a median followup period of 270 days (74.3% vs 57.3%, P = 0.021). Yin et al [2006] compared the efficacy, in the long term, of amiodarona at a low dose (200 mg) alone, or combined with losartan or perindopril, in the prevention of the recurrence of paroxysms in isolated AF in 177 patients after 24 months of follow-up. AF recurrence was found to be 41, 19, and 24%, respectively (P = 0.02).…”
Section: Therapeutic Advances In Cardiovascular Diseasementioning
confidence: 99%